A Century of Diabetes Technology: Signals, Models, and Artificial Pancreas Control. (July 2019) - Kovatchev, Boris
Abstract : Arguably, diabetes mellitus is one of the best-quantified human conditions: elaborate in silico models describe the action of the human metabolic system; real-time signals such as continuous glucose monitoring are readily available; insulin delivery is being automated; and control algorithms are capable of optimizing blood glucose fluctuation in patients' natural environments. The transition of the artificial pancreas (AP) to everyday clinical use is happening now, and is contingent upon seamless concerted work of devices encompassing the patient in a digital treatment ecosystem. This review recounts briefly the story of diabetes technology, which began a century ago with the discovery of insulin, progressed through glucose monitoring and subcutaneous insulin delivery, and is now rapidly advancing towards fully automated clinically viable AP systems. Highlights: Classic studies have shown that the complications of diabetes can be reduced by strict glycemic control. However, the risk of hypoglycemia remains the primary barrier to intensive therapy; thus, people with diabetes face a life-long optimization problem: reduce their HbA1c while simultaneously avoiding hypoglycemia. Contemporary technologies, such as CGM and CLC (known as the AP), offer the best solution to this optimization problem, particularly in type 1 diabetes. The advancement of these technologies is enabled by decades of studies aiming to develop elaborate in silico models describing the action of the human metabolic system, process CGM data and other metabolic signals, and automate insulin delivery. As a result, 100 years after the discovery of insulin, the technology is entering the stage of fully automated portable AP systems providing real-time, long-term optimal control of diabetes in patients' natural environments.